Analysis of Instagram Content “@Juniata_Siregar” In Online Arabic Language Learning - Siti Tsamrotul Fuady; Yuyun Rohmatul Uyuni; Siti Shalihah (Journal of Educational Sciences, 2026)
The advancement of digital technology has transformed the paradigm of language learning, including Arabic, from conventional methods toward a more interactive, social media based approach. Instagram, as one of the most popular platforms, is now utilized by Arabic language educators to deliver learning materials in a creative and engaging way. This study aims to analyze Arabic learning content posted by the Instagram account @juniati_siregar, focusing on content presentation strategies, linguistic aspects, and audience engagement. The research employs a qualitative descriptive content analysis method, with data collected through observation of posts published between January and July 2025. The results indicate that the content produced by Juniati Siregar predominantly features themes of vocabulary (mufradāt), daily expressions (ta‘bīrāt), and basic grammar (nahwu-ṣaraf), which are presented attractively through visual illustrations, bilingual captions (Arabic-Indonesian), and pronunciation audios. The strategic use of reels and infographics effectively enhances follower interaction, particularly in posts that demonstrate language use in communicative contexts. In conclusion, the @juniati_siregar account successfully offers an adaptive model for Arabic language learning in the digital era through an edutainment approach, serving as a valuable reference for teachers and learners in optimizing social media as a platform for independent and collaborative learning.